2022
DOI: 10.1177/11206721221141481
|View full text |Cite
|
Sign up to set email alerts
|

Management of inflammation in dry eye disease: Recommendations from a European panel of experts

Abstract: Introduction Early initiation of anti-inflammatory therapies is recommended for dry eye disease (DED) to break the vicious cycle of pathophysiology. However, there is limited guidance on how to implement topical ciclosporin (CsA) and corticosteroid treatment into clinical practice. This expert-led consensus provides practical guidance on the management of DED, including when and how to use topical CsA. Methods A steering committee (SC) of seven European DED experts developed a questionnaire to gain information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…TFOS DEWS II management reported that many treatment options for dry eye are poorly supported by level I studies [ 6 ]. Nevertheless, environmental and dietary modifications, elimination of offending factors, artificial tears, ointment, topical agents including corticosteroids, secretagogues, immunomodulators, and blood derivatives, lid hygiene, warm compress, punctal occlusion, IPL, and thermal pulsation therapy, etc., are helpful for dry eye patients [ 6 , 8 , 9 , 30 ]. Previous treatment guidelines by the KCDSG presented a stepladder approach according to severity level [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…TFOS DEWS II management reported that many treatment options for dry eye are poorly supported by level I studies [ 6 ]. Nevertheless, environmental and dietary modifications, elimination of offending factors, artificial tears, ointment, topical agents including corticosteroids, secretagogues, immunomodulators, and blood derivatives, lid hygiene, warm compress, punctal occlusion, IPL, and thermal pulsation therapy, etc., are helpful for dry eye patients [ 6 , 8 , 9 , 30 ]. Previous treatment guidelines by the KCDSG presented a stepladder approach according to severity level [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with persistent inflammation of the ocular surface may require immune modulating agents such as ciclosporin63637 or tacrolimus 383940 to avoid long term use of topical steroids. Both these treatments have been inconsistently reported to induce long lasting symptom improvement and may be safely used for prolonged periods 6414243. A recent randomised controlled trial comparing the efficacy of topical ciclosporin versus tacrolimus for dry eye disease demonstrated equivalency between the two 44.…”
Section: Treatment Of Specific Causesmentioning
confidence: 99%
“…A recent study by Fondi K et al [ 63 ] demonstrated that eye drops with a combination of hydrocortisone and ciclosporin A improved patients‘ symptoms and might be beneficial for long-term and improved vision quality among SS DED patients. In addition, patients’ tolerability is critical in choosing the type of corticosteroid to be used in managing DED symptoms [ 58 , 64 ].…”
Section: Medicaments In the Management Of Dedmentioning
confidence: 99%